A family of faith an introduction to evangelical Christianity - Phillips, Timothy Ross, 1950-2000; Okholm, Dennis L. (Grand rapids, MI Baker, 2001)
Includes bibliographical references and index.
First published, 1996 as "Welcome to the family"
Keywords: Evangelistic work -- history; Evangelicalism